2018
DOI: 10.4066/biomedicalresearch.29-17-3756
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age and BMI on oocyte maturation and embryo development

Abstract: Background: Ovarian oogenesis is under the control of gonadotropins. In the human ovary, each fully grown oocyte resumes maturation in response to gonadotrophins. This process is completed after oocytes reach metaphase stage of second meiotic division (MII) stage. The aim of this prospective, clinical trial was to perceive the age and BMI effect on oocytes maturation and embryos development in women undergoing control ovarian hyperstimulation. Method: A total of 40 infertile women undergoing ovarian hyperstimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…The observations were contrary to the study by (Al-Obaidi, et al [11] ) which showed that triggering day were markedly high with progesterone elevation than in the nonprogesterone elevation groups (Wu, et al [14] ). The explanation is that, when FSH is used in stimulation, it induces bearing of LH receptors in granulosa cells, which leads to increase sensitivity to the same LH, which in turn could conduct to create the rise of progesterone prematurely, even with low level of serum LH (Glamoclija, et al [15] ).…”
Section: Discussioncontrasting
confidence: 91%
“…The observations were contrary to the study by (Al-Obaidi, et al [11] ) which showed that triggering day were markedly high with progesterone elevation than in the nonprogesterone elevation groups (Wu, et al [14] ). The explanation is that, when FSH is used in stimulation, it induces bearing of LH receptors in granulosa cells, which leads to increase sensitivity to the same LH, which in turn could conduct to create the rise of progesterone prematurely, even with low level of serum LH (Glamoclija, et al [15] ).…”
Section: Discussioncontrasting
confidence: 91%
“…The present study displayed the absence of a significant difference in mean age between pregnant and non-pregnant women, which agreed with the result of (Zhang, Bu, Su, & Sarah Hamza Herez, et al: Effect of Bisphenol A Level in Follicular Fluid on ICSI OutCome Zhu, 2018) who noted a reasonable low outcome in women aged 35-37 years during the first three ovarian stimulation cycles. In opposite other studies concluded that the female age is the fundamental predictor of pregnancy after assisted reproduction technique and there is a negative relation between increasing female age and the success rate of ICSI (Al-Obaidi, Mahdi, & Alwasiti, 2018;Fahad, Al-Murshedi, & Al-Khafaji, 2015). Also, the comparison between the Pregnant and Non-Pregnant women, showed that there were no significant differences in other demographic characteristics, namely body mass index (BMI), residency, educational level, occupation, lifestyle habits, type, and duration of infertility, and history of previous IVF treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Women, ages 20–24 yr old have the best ability to get pregnant; after age 30, a progressive decline in this ability occurs with age ( 2 , 3 ). Both the gradual depletion of oocytes and the reduction in oocyte quality, at least after the age of 31, are important reasons for decreased fertility capacity ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%